2015
DOI: 10.1089/lap.2015.0308
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Transperitoneal Approach to Robot-Assisted Laparoscopic Partial Nephrectomy for the Treatment of Anterior and Posterior Renal Masses

Abstract: The transperitoneal approach to partial nephrectomy for posterior tumors resulted in no difference in operative time, WIT, EBL, LOS, positive surgical margins, reduction in eGFR, or postoperative complications. The TPRPN approach to treat a posterior tumor is reasonable and is the preferred technique at our institution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Two retrospective studies have found no difference in peri‐operative outcomes for anterior versus posterior tumours via the transperitoneal approach [27,28]. Similarly, in this series of retroperitoneal RAPN, we found no differences in outcomes for anterior tumours compared with posterior or lateral tumours.…”
Section: Discussionsupporting
confidence: 67%
“…Two retrospective studies have found no difference in peri‐operative outcomes for anterior versus posterior tumours via the transperitoneal approach [27,28]. Similarly, in this series of retroperitoneal RAPN, we found no differences in outcomes for anterior tumours compared with posterior or lateral tumours.…”
Section: Discussionsupporting
confidence: 67%
“…Similar to others, our data shows that the RP approach is associated with less EBL than its TP counterpart 7 , 10 , 11 , 14 17 This was borne out in a recent meta-analysis, although other individual studies have found similar EBL between the two approaches. 9 , 18 , 19 …”
Section: Discussionmentioning
confidence: 99%
“…Similar to others, our data shows that the RP approach is associated with less EBL than its TP counterpart 7,10,11,[14][15][16][17] This was borne out in a recent meta-analysis, although other individual studies have found similar EBL between the two approaches. 9,18,19 A 2020 paper investigating the use of the TP and RP approaches in the treatment of 566 patients from a single surgeon showed that the two groups of patients had similar Pentafecta (i.e., negative surgical margins, no postoperative complications, warm ischemia time ≤ 25 minutes, over 90% eGFR preservation, and no chronic kidney disease progression 1 year after surgery) achievement rates. 15 In a sub-analysis assessing anterior lesions, they reported no difference in the T stage, RENAL score complexity, or histology for anterior lesions treated with TP or RP approach, which is similar to our experience.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have addressed the surgical feasibility of RAPN for anterior or posterior renal masses, as we did. 3,4 Harris and colleagues analyzed 260 patients who underwent transperitoneal RAPN with 92 cases of posterior tumors and 168 cases of anterior tumors. They demonstrated no significant difference in operative time, WIT, EBL, PLOS, positive surgical margins, reduction in eGFR, and postoperative complications according to tumor position.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 There are few reports analyzing the impact of kidney function in the acute postoperative period according to tumor position, such as anterior or posterior, specifically in transperitoneal RAPN. 3,4 In the present study, we compared surgical outcomes, including early postoperative renal function after transperitoneal RAPN between anterior and posterior tumors, using propensity score matched analyses.…”
Section: Introductionmentioning
confidence: 99%